Empowerment of the Malay language issues, rationales and challenges of the Malaysian ministry of education - Irma Wani Othman; Anna Lynn Abu Bakar; Mohd Sohaimi Esa (Global Academic Excellence, 2022)
The focus of the discussion in this paper is about the use of the Malay language among plural societies in Malaysia. This writing attempts to cover the empowerment of the Malay language that is being worked on by the Ministry of Higher Education, which includes (i) the mastery of the Malay language regardless of race or ethnicity, (ii) the ability and authority of the Malay language, (iii) the organization and strengthening of programs to dignify the Malay language, and (iv) the use of the Malay language as the medium of communication. The use of a qualitative approach in this writing utilizes secondary sources such as research results in journals, scholarly writing, online news sources and public forums. The results of the study found that (a) the use of English today as the first medium in speech is a contributing factor to the lack of use of the mother tongue among the multi-ethnic community in Malaysia and instils an individualistic attitude., (b) the use of the Malay language in the private sector has not been prominent because there are a few parties who think that the Malay language has a low commercial value in the business sector, (c) Malay language empowerment programs play a vital role in catalysing the fluency of students as well as the administrative parties at the school and university level so that, issues such as lack of fluency and the dignity of the use of the Malay language as an official language that should be mastered by every Malaysian citizen can be improved and streamlined and (d) If Malay is not used as a medium of instruction, it is unlikely that it will be able to stand majestically on the world stage. As a result, drastic measures must be taken to ensure that the empowerment of the Malay language is in line with the country's development and does not fall solely on the shoulders of the Ministry of Education and Culture. The study's direction looks at the continuation of the impact of the Malay language's empowerment as a language of unity and one of the mediums that play a role in realising our country's aspirations, which is to create racial harmony.